Visual acuity of budgerigars for moving targets - Sandra Chaib; Juliane Gaviraghi Mussoi; Olle Lind; Almut Kelber (Biology Open, 2021)
For a bird, it is often vital to visually detect food items, predators, or individuals from the same flock, i.e. moving stimuli of various shapes. Yet, behavioural tests of visual spatial acuity traditionally use stationary gratings as stimuli. We have behaviourally tested the ability of budgerigars (Melopsittacus undulatus) to detect a black circular target, moving semi-randomly at 1.69 degrees s−1 against a brighter background. We found a detection threshold of 0.107±0.007 degrees of the visual field for a target size corresponding to a resolution of a grating with a spatial frequency of 4.68 cycles degree−1. This detection threshold is lower than the resolution limit for gratings but similar to the threshold for stationary single objects of the same shape. We conclude that the target acuity of budgerigars for moving single targets, just as for stationary single targets, is lower than their acuity for gratings.